The patient's perspective: The effect of levodopa on Parkinson symptoms. (February 2017) - Zach, Heidemarie; Dirkx, Michiel; Pasman, Jaco W.; Bloem, Bastiaan R.; Helmich, Rick C.
Abstract: Background: Dopaminergic medication adjustments in Parkinson's disease are often solely based on patient reports. However, it is unclear how well patient-based ratings of the levodopa response correlate with clinician-based ratings, and whether this correlation differs between motor symptoms. Here we compare patient-clinician agreement for the effect of levodopa on resting tremor and bradykinesia/rigidity. Furthermore, given patients' reports that tremor is most troublesome during stress, we test for differences in patient-clinician agreement between tremor at rest and stress-induced tremor. Methods: We included 42 tremulous Parkinson patients, who were clinically rated (using the MDS-UPDRS) in a practically defined OFF-state and after levodopa-benserazide 200/50 mg. Using accelerometry, we quantified the effect of dopaminergic medication and behavioral context (rest vs. cognitive stress) on tremor intensity. Patients rated medication effects on tremor and bradykinesia/rigidity using visual analogue scales. Results: There was only moderate patient-clinician agreement for the effect of levodopa on bradykinesia/rigidity (R 2  = 0.18; p < 0.01), and a tendency towards larger agreement for tremor (R 2  = 0.44; p < 0.001; difference between correlation coefficients: z = 1.64; p = 0.051). Patient ratings of tremor changes correlated significantly better with accelerometry for tremor during cognitive stress (R 2  = 0.35; p < 0.001) vs. tremor at rest (R 2  = 0.12; p < 0.05; difference: z = −2.35, p < 0.01). Conclusion: The moderate correlations between patient ratings and clinical/accelerometry changes indicate the need for methods to better monitor symptom severity and impairments in daily life, for example wearable sensors. Our findings also suggest that context matters: Parkinson patients' subjective experience of levodopa effectiveness on tremor was largely based on the ability of levodopa to reduce tremor during cognitive stress. Highlights: We investigated the agreement between patients and clinicians about the dopamine response in Parkinson's disease. Parkinson patients judge the effect of levodopa by its ability to reduce stress-induced tremor. Patients weigh the dopamine response of different symptoms in a different way. The combination of medical assessments and patients' ratings in clinical practice and in scientific research is crucial.